Length-Weight relationship and Condition Factor of Sardinella gibbosa (Bleeker, 1849) from the North-West Coast of Sri Lanka - Chanaka Supun Bandara Pallemulla, P.M.R.; Kuganathan, S.; Santos, J.; Jayasinghe, P. (University of Jaffna, 2024)
The present study aimed to determine the length-weight relationship and condition factor of Sardinella gibbosa (Bleeker, 1849) on the North-West coast of Sri Lanka. The samples were collected every month from three major fish landing centers between 2021-2023. The fish were caught in a small mesh (1.27 cm - 3.81 cm) gill net. The average weight of S. gibbosa ranged from 4.2 g to 28.1 g, with a mean of 15.77 g. The length ranged from 6.2 cm to 14.3 cm, with an average of 9.65 cm. The length-weight relationship, W=aLb and condition factor (W *100/L3) are presented for the S. gibbosa. The length-weight relationship of the sardines collected from Chilaw, Negombo, and Puttalam sampling areas were W=0.11328L2.085 (R2=0.7208), W=0.0927L2.3319 (R2=0.7667), and W=0.0926L2.3562 (R2=0.7586), respectively. The condition factor ranged from 1.467 to 1.484 and the regression coefficient indicated negative allometric growth. The data obtained can be used as a baseline for future studies and valuable source for fisheries managers, biologists, and conservationists to save the fisheries resources.
Keywords: Length-weight relationship; Sardinella gibbosa; Condition factor; Allometric growth